Pengaruh Brand Equity, Customer Value dan Price terhadap Repurchase Intention Konsumen Indomie di Kota Semarang - Aditya, Dhimas; Nuryanto, Imam (Jurnal Ekonomi dan Bisnis, 2024)
Repurchase intention is a behavior of people who buy products repeatedly which arises because of a previous feeling of satisfaction. Repurchase interest is part of purchasing behavior where in the context of repurchase interest there is the concept of loyalty. Many factors influence repurchase intention, including brand equity, customer value and price. The main objective of this research is to test and analyze the influence of brand equity, customer value and price on the repurchase intention of Indomie consumers in Semarang City. The population is the entire population in Semarang City who have Repurchase Intention on Indomie products. The sample for this research was 119 respondents. The sampling technique is purposive sampling. Verification analysis in this research uses statistical testing tools, namely the variance-based structural equation test or better known as SEM-Partial Least Square (PLS). The results of this research show that brand equity has a positive and significant effect on the repurchase intention of Indomie consumers in Semarang City. Customer value has a positive and significant effect on the repurchase intention of Indomie consumers in Semarang City. Price has a positive and significant effect on the repurchase intention of Indomie consumers in Semarang City. Repurchase intention merupakan salah satu perilaku masyarakat yang membeli produk secara berulang yang timbul karena adanya rasa kepuasan sebelumnya. Minat beli ulang merupakan bagian dari perilaku pembelian dimana didalam konteks minat beli ulang tersebut terdapat konsep loyalitas. Banyak faktor yang mempengaruhi repurchase intention, diantarana adalah brand equity, customer value dan price. Tujuan utama penelitian ini adalah untuk menguji dan menganalisis pengaruh brand equity, customer value dan price terhadap repurchase intention konsumen Indomie di Kota Semarang. Populasi adalah keseluruhan masyarakat di Kota Semarang yang melakukan repurchase intention pada produk Indomie. Sampel penelitian ini sebanyak 119 responden. Teknik pengambilan sampel secara purposive sampling. Analisis verifikatif dalam penelitian ini menggunakan alat uji statistik yaitu dengan uji persamaan struktural berbasis variance atau yang lebih dikenal dengan nama SEM-Partial Least Square (PLS). Hasil penelitian ini menunjukkan bahwa brand equity berpengaruh positif dan signifikan terhadap repurchase intention konsumen Indomie di Kota Semarang. Customer value berpengaruh positif dan signifikan terhadap repurchase intention konsumen Indomie di Kota Semarang. Price berpengaruh positif dan signifikan terhadap repurchase intention konsumen Indomie di Kota Semarang. Keywords: Brand Equity Customer Value PriceRepurchase Intention